2016
DOI: 10.21037/jtd.2016.03.70
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of neural respiratory drive for the assessment of bronchodilator responsiveness in patients with chronic obstructive pulmonary disease: an exploratory study

Abstract: Background: Conventional lung function parameters, such as forced vital capacity (FVC), forced expiratory volume in 1 second (FEV 1 ) and inspiratory capacity (IC) are often used to assess the therapeutic outcomes of bronchodilators, but they lack sensitivity. A novel indicator, namely efficiency of neural respiratory drive (NRD), may objectively evaluate the physiological changes in patients with chronic obstructive pulmonary disease (COPD). We investigated whether this indicator could be used to more accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“… 26 In this way, Reilly et al demonstrated in cystic fibrosis patients how neural drive, measured by EMGpara, decrease to a great extent (−39%) after an infectious exacerbation resolves. 12 In a similar way, neural drive measured by EMGpara has been proposed as a tool to evaluate the effectiveness of bronchodilators 27 or even as marker of hyperinflation. In this latter topic, neural respiratory drive may reflect mechanics impairment in COPD patients, mainly related to expiratory flow limitation and hyperinflation.…”
Section: Discussionmentioning
confidence: 99%
“… 26 In this way, Reilly et al demonstrated in cystic fibrosis patients how neural drive, measured by EMGpara, decrease to a great extent (−39%) after an infectious exacerbation resolves. 12 In a similar way, neural drive measured by EMGpara has been proposed as a tool to evaluate the effectiveness of bronchodilators 27 or even as marker of hyperinflation. In this latter topic, neural respiratory drive may reflect mechanics impairment in COPD patients, mainly related to expiratory flow limitation and hyperinflation.…”
Section: Discussionmentioning
confidence: 99%
“…These indices could be also of potential value to evaluate therapeutic interventions, such as inhaled bronchodilators, noninvasive ventilation, or inspiratory muscle training, aimed at reducing intrinsic respiratory mechanical loading in COPD patients [36]. Indeed, the efficiency of NRD, defined as the ratio of minute ventilation to the root mean square of invasive oesEMG di measures, has been demonstrated to be a sensitive index to evaluate the response to inhaled bronchodilators in COPD, with significant improvements reported after bronchodilation [37]. The application of the noninvasive indices proposed in this study in evaluating treatment benefits could therefore be a subject of future research.…”
Section: Discussionmentioning
confidence: 99%
“…The change in the neural respiratory drive (NRD) has been used to evaluate the efficacy of several drugs (16,17), and to predict the risk of acute exacerbation of COPD (18). Noninvasive positive pressure ventilation (NPPV) is to overcome airway resistance and improve ventilation, thereby reduce the work of breathing and the burden on the respiratory muscle, and facilitate sufficient rest of fatigued respiratory muscle (19,20).…”
Section: Discussionmentioning
confidence: 99%